The costs of diversifying the principal workforce: Black jobs, Black principal(ing), and sustainability - Stanley, Darrius A. (Frontiers in Education, 2025)
IntroductionA recent statewide principal survey revealed that Black principals are more likely than white and other principals of color to frame their workload as unsustainable. Scholarship suggests that Black principals specifically lack district-level support when navigating racialized resistance to their leadership from white faculty and families. Hence, this empirical scholarship examines the lived, racialized experiences of four Black principals working in historically and predominantly white school districts in Minnesota.MethodsSpecifically, this scholarship leverages qualitative methods (e.g., interviews) to understand Black principal’s perceptions of sustainability in the principalship; the nature of resistance from white families, faculty, and staff; the organizational working conditions (e.g., district supports); and their career plans within the district and/or profession.ResultsThree themes emerged from this data: 1) Black social suffering, 2) Costs, and 3) District (Un)readiness.DiscussionThis scholarship offers important implications for increasing the sustainability and support of Black principals within the field. Moreover, it provides critical insight into how district leaders can and should specifically support Black principals and interrupt school, district, and community-based, anti-Black resistance.